LSD1 inhibition induces differentiation and cell death in Merkel cell carcinoma - Lukas Leiendecker; Pauline S Jung; Izabela Krecioch; Tobias Neumann; Alexander Schleiffer; Karl Mechtler; Thomas Wiesner; Anna C Obenauf (EMBO Molecular Medicine)
Abstract Merkel cell carcinoma (MCC) is a highly aggressive, neuroendocrine skin cancer that lacks actionable mutations, which could be utilized for targeted therapies. Epigenetic regulators governing cell identity may represent unexplored therapeutic entry points. Here, we targeted epigenetic regulators in a pharmacological screen and discovered that the lysine‐specific histone demethylase 1A (LSD1/KDM1A) is required for MCC growth in vitro and in vivo. We show that LSD1 inhibition in MCC disrupts the LSD1‐CoREST complex leading to displacement and degradation of HMG20B (BRAF35), a poorly characterized complex member that is essential for MCC proliferation. Inhibition of LSD1 causes derepression of transcriptional master regulators of the neuronal lineage, activates a gene expression signature resembling normal Merkel cells, and induces cell cycle arrest and cell death. Our study unveils the importance of LSD1 for maintaining cellular plasticity and proliferation in MCC. There is also growing evidence that cancer cells exploit cellular plasticity and dedifferentiation programs to evade destruction by the immune system. The combination of LSD1 inhibitors with checkpoint inhibitors may thus represent a promising treatment strategy for MCC patients.